Determinants of Financial Development - Huang, Yongfu (Springer Nature, 2010)
"As the world has witnessed the worst financial crisis and climate crisis of our age, during the period of 2007-2009, the issues surrounding the emergence and development of financial markets and carbon markets is becoming an increasingly significant area of research and debate worldwide. By engaging with recently developed methods of research and new areas of practice, this book investigates the political, economic, policy and geographic determinants of the development of financial markets. The volume examines the causality between financial development and aggregate private investment from an economic perspective. It also explores the consequences of political liberalization, focusing on the impact of institutional improvement on financial development. It studies what stimulates governments to initiate reforms aimed at boosting financial development, and analyses the determinants of carbon markets in developing countries from a geographic point of view. This book is essential reading for all interested in economic and financial development, climate change, environmental economics, and applied econometrics. "